A Fragment from the Reign of Tausret Reused at Medinet Habu - McClain, J. Brett.
A sandstone fragment in the blockyard at Medinet Habu (MH bl. 0936) shows two stages of carving on adjoining faces, the later of which, bearing the names of Ramesses III, is part of a frieze from the destroyed inner chambers of his mortuary temple. The earlier inscription is found to contain the name and royal titles of Tausret, with cartouches erased but not reinscribed, and it is shown that this block must originally have come from her destroyed mortuary temple. This piece thus demonstrates for the first time that Tausret’s temple was dismantled for building material and its blocks reused in the Medinet Habu complex early in Ramesses III’s reign.